Priamel v grški književni tradiciji in enumeracija v indoevropščini - Galjanić, Ana (Array, 2009)
This paper examines the structure of a Greek poetic genre called the ‘priamel’, comparing it with similar constructions in cognate literary traditions and arguing that it is not an isolated poetic phenomenon by identifying several structurally parallel passages in Vedic, Welsh and Serbo-Croatian literatures. Placing the priamel within the larger context of poetic enumerations, the study points out the underlying typological correspondences between the priamel and a specific type of poetic list called a ‘bounded set’.